A Study of Physical and Mechanical Properties of Nata de Coco in the Market. (August 2019) - Rahmayanti, Handika Dany; Amalia, Nadya; Munir, Rahmawati; Yuliza, Elfi; Utami, Fisca Dian; Sustini, Euis; Abdullah, Mikrajuddin
Abstract: Nata de coco is a bacterial cellulose produced by Acetobacter xylinum in the process of fermenting coconut water. It is renowned for its high fiber content. The chewiness of nata de coco is proportional to the fiber content. There are many brands of nata de coco available in the market. Six different brands are included in this study. The mechanical strengths have been evaluated using a Universal Testing Machine. Based on the tensile test results, the lowest Young's modulus is 3 MPa, attributed to the brand labeled as F as the most elastic nata de coco among the six brands. The degree of elasticity of nata de coco also corresponds to the sugar content. Further, the optical properties have been observed using a UV/Vis Spectrometer. Clearer nata de coco yields higher transmittance value. Meanwhile, the turbidity commensurate the nitrogen content.